1986
DOI: 10.3109/02713688609015127
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationship between intraocular pressure and Honan Intraocular Pressure Reducer pressure

Abstract: The relationship between the pressure applied to the enucleated human eye using the Honan Intraocular Pressure Reducer (HIPR) and the peak intraocular pressure as a function of initial intraocular pressure has been examined. The peak intraocular pressure is linearly related to the applied HIPR pressure whether the latter is 30, 50, or 75 mm Hg. The slopes relating peak intraocular pressure to initial intraocular pressure at different HIPR settings are parallel. Use of the HIPR at settings greater than 30 mm Hg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Factors, e.g. scleral rigidity, ocular curvature, pressure-volume relationships etc, all vary between species and tonometers must be calibrated for each species (Green 1990). In addition, the PT exerts a higher force on a small area, which increases the IOP at the moment of measurement.…”
Section: In Vitro Modelmentioning
confidence: 99%
“…Factors, e.g. scleral rigidity, ocular curvature, pressure-volume relationships etc, all vary between species and tonometers must be calibrated for each species (Green 1990). In addition, the PT exerts a higher force on a small area, which increases the IOP at the moment of measurement.…”
Section: In Vitro Modelmentioning
confidence: 99%
“…In our study, ocular compression using a HIPR was set to 30 mmHg for 10 min. In their experimental study, Green et al [33] report that a 30-mmHg HIPR setting did not increase the IOP excessively, and McDonnell et al [34] report that the Honan device appeared to be safe for eyes undergoing routine anterior segment surgery, but the pressure that may be generated in hypertensive eyes (IOP [35 mmHg) could put these eyes at risk of vascular occlusion. Thus, we suggest that routine IOP examination be performed before any application of the HIPR is attempted.…”
Section: Discussionmentioning
confidence: 97%
“…In the current study, the ocular compression was set to 30 mmHg for 10 minutes. Green et al reported that HIPR setting of the 30 mmHg does not cause an excessive IOP elevation in their experimental study (20). McDonnell et al demonstrated that the Honan device would appear to be safe for eyes undergoing routine anterior segment surgery, but the pressures that may be generated in hypertensive eyes (IOP greater than or equal to 35 mmHg) might put these eyes at risk for vascular occlusion (21).…”
Section: Effect Of the Intraocular Pressure Reducer On Vitreous Refluxmentioning
confidence: 99%
“…The Honan intraocular pressure reducer (HIPR) is a device that has been used to reduce IOP during cataract surgery (18, 19). The HIPR can reduce the IOP through vitreous volume reduction by virtue of ocular compression (20, 21). The purpose of this prospective study was to determine whether or not preoperative IOP reduction using the HIPR can reduce the amount of vitreous reflux after IVT injection.…”
Section: Introductionmentioning
confidence: 99%